FFTHR: Fitness Function based Two‐Hop Routing in WSN. Issue 4 (25th August 2020) - Panchal, Akhilesh; Singh, Rajat K.
Abstract : In Wireless Sensor Networks (WSNs), the Cluster Heads (CHs) are used for efficient data collection from the enormous number of randomly deployed sensor nodes. Since these CHs consume a massive amount of energy and degrade the lifetime of the network, thus reducing their energy consumption is the prime concern. In order to enhance the network lifetime, we are proposing the Fitness Function‐based Two‐Hop Routing (FFTHR) algorithm for inter‐cluster routing among all the CHs of the network. This algorithm depends on the residual energy of the CHs and their relative Equlidean distances from the Base Station (BS) as well as from their centroid. One of the CHs has been defined here as Central Cluster Head (CCH) based on their fitness value, and it uses single‐hop for transmitting their data packets to the BS while the remaining CHs use two‐hop. The simulation results exhibit that the FFTHR enhances the network lifetime and saves the energy consumption of the network as compared to the similar algorithm for example, REHR (Residual Energy based Hybrid Routing) and FCM (Fuzzy C‐Means).